The Impact of Mental Health on Work Productivity in The Workplace - Sadat, Lubna Anwar; Afrizal, Adheelah Rachmah (Syntax Corporation Indonesia, 2023)
Human resources are one of the important factors in achieving company goals. Companies need to do human resource management well, need to pay attention to the condition of each employee so that human resources can continue to work with high work productivity in the workplace. The purpose of this study was to determine the impact of mental health on work productivity in the workplace of employees. The research method used is quantitative method. The results showed that mental health has a positive effect on work productivity in the workplace. Mental health is the main concern of the company in addition to physical health. As for some aspects of mental health that affect work productivity include concentration and focus, high stress levels, motivation and work enthusiasm, task completion effectiveness, attendance and absenteeism, and work relationships.